Risk of Inflammatory Bowel Disease in Patients With Psoriasis and Psoriatic Arthritis/Ankylosing Spondylitis Initiating Interleukin‐17 Inhibitors: A Nationwide Population‐Based Study Using the French National Health Data System. Issue 2 (27th January 2022) - Penso, Laetitia; Bergqvist, Christina; Meyer, Antoine; Herlemont, Philippe; Weill, Alain; Zureik, Mahmoud; Dray‐Spira, Rosemary; Sbidian, Emilie
Abstract : Objective: To investigate whether the initiation of treatment with an interleukin‐17 inhibitor (IL‐17i) in real life is associated with a higher risk of inflammatory bowel disease (IBD) in patients who had both psoriasis (PsO) and psoriatic arthritis (PsA)/ankylosing spondylitis (AS). Methods: This nationwide cohort study was conducted using the French National Health Data System database. All adult patients with PsO and PsA/AS who were identified as having newly initiated treatment with an IL‐17i during 2016–2019 were included. As controls, patients with PsO and PsA/AS who had newly initiated either 1) apremilast or 2) etanercept (ETN) during this period but had not received IL‐17i were included. The follow‐up end date was September 30, 2019. The primary end point was the risk of occurrence of IBD associated with exposure to an IL‐17i compared to exposure to the other treatments, as determined in a time‐to‐event analysis with propensity score–weighted Cox and Fine‐Gray proportional hazards models. Results: The study included a total of 16, 793 new IL‐17i users (mean ± SD age 48.4 ± 13 years, 45% men), 20, 556 new apremilast users (age 52.6 ± 15 years, 54% men), and 10, 294 new ETN users (age 46.3 ± 15 years, 44% men). New IL‐17i users and new ETN users had received more biologics for their underlying disease compared to new apremilast users. IBD occurred in 132 patients: 72 new IL‐17i users (0.43%), 11 new apremilast users (0.05%), and 49 new ETN users (0.48%). Most IBD cases occurred after 6 months of exposure (82%, 55%, and 76%, respectively). After propensity score weighting, the risk of IBD was significantly greater among patients initiating an IL‐17i compared to those initiating apremilast (weighted hazard ratio [HR] 3.8 [95% confidence interval (95% CI) 2.1–6.8]). No difference in the risk of IBD between new IL‐17i users and new ETN users was observed (weighted HR 0.8 [95% CI 0.5–1.2]). Conclusion: Patients with PsO and PsA/AS who initiate treatment with an IL‐17i do not have a higher risk of developing IBD when compared to patients initiating ETN who display the same severity of underlying disease. These results need to be confirmed in other large studies of patients with PsO and PsA/AS.